2006
DOI: 10.1007/s10144-006-0008-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological considerations for biological control of aphids in protected culture

Abstract: Several braconid and aphelinid parasitoids, midges, lacewings, and ladybird beetles are used to control aphids in greenhouses. Here, I review three topics as ecological bases for the biological control of aphids in a protected culture: the preliminary evaluation of biological control agents, natural enemy release strategies, and the effects of intraguild predation (IGP) on biological control. A comparison of several parasitoid species was conducted to select agents for the biological control of aphids; the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 18 publications
1
42
0
2
Order By: Relevance
“…In contrast, recent glasshouse experiments indicated that H. axyridis complemented biocontrol of Macrosiphum euphorbiae by the parasitoid Aphelinus asychis (Snyder et al, 2004b) (2006) concluded from other outdoor experiments that IGP is often unimportant in the field and warn that the results of laboratory IGP experiments should be interpreted with caution. Yano's (2006) review suggests that IGP may be even less important to biological control in protected culture than in the field.…”
Section: Intraguild Relationsmentioning
confidence: 99%
“…In contrast, recent glasshouse experiments indicated that H. axyridis complemented biocontrol of Macrosiphum euphorbiae by the parasitoid Aphelinus asychis (Snyder et al, 2004b) (2006) concluded from other outdoor experiments that IGP is often unimportant in the field and warn that the results of laboratory IGP experiments should be interpreted with caution. Yano's (2006) review suggests that IGP may be even less important to biological control in protected culture than in the field.…”
Section: Intraguild Relationsmentioning
confidence: 99%
“…Entomopathogenic nemotades such as Steinernema feltiae (Nematoda: Steinernematidae) are a compatible and effective option for use with predatory mites to control WFT. Nematodes are a good option in a biological control strategy involving predatory mites, because they primarily attack the soil-dwelling pupal stage of WFT (Buitenhuis & Shipp, 2005;Ebssa et al, 2004;2006), leaving the larval stages for predatory mites. Emergence of adult WFT was significantly reduced when the predatory mite G. aculeifer was added to bean seedlings along with two species of entomopathogenic nematodes, than either mite or nematode treatment alone (Premachandra et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…(Gerson & Weintraub, 2007;Heinz et al, 2004;Yano, 2006). However, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), commonly known as western flower thrips (WFT), is the most important insect pest of greenhouse ornamental production (Buitenhuis et al, 2007;Heinz et al, 2004).…”
Section: Insect Pests Of Ornamental Greenhouse Cropsmentioning
confidence: 99%
“…Thus, growers are at risk of introducing natural enemies too late. In order to overcome this risk, introductions can be made by means of a banker plant system, or an open-rearing system (Hansen, 1983;van Lenteren and Woets, 1988;Yano, 2006). Prior to pest occurrence, banker plants serve as a reservoir of control agents in the greenhouse by providing them with an alternative, non-pest food source.…”
Section: Introductionmentioning
confidence: 99%